O impacto do uso intraoperatório de opioides na sobrevida de indivíduos submetidos a cirurgia para Glioblastoma Multiforme - Naufal, Rodrigo Ferrari Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The impact of intraoperative use of opioids on the survival of individuals undergoing surgery for Glioblastoma multiforme Abstract Introduction: Glioblastoma multiforme is a primary malignant tumor of the Central Nervous System (CNS) and one of the most aggressive tumors that can affect humans, with no cure so far and with an extremely reverse prognosis with an average survival that varies from 7 to 15 months. Recently, the role of opioids used in cancer surgery, has been related to the progression and spread of the disease. The objective is to investigate the influence of intraoperative opioid use in glioblastoma surgery on disease-free survival and overall survival of these patients. Methods: Observational and retrospective study, with analysis of medical records of 133 patients who underwent 167 surgical procedures for resection of Glioblastoma Multiforme. The inclusion and exclusion criteria were as follows: patients older than 18 years of age, of both sexes, who has operated for brain tumor with anatomopathological diagnosis of glioblastoma multiforme. Patients who died in the postoperative period from causes unrelated to the underlying disease were excluded, as were patients who did not have specific data on the drugs used in the perioperative period in their records. The following variables were analyzed: onset of symptoms, age, pre-and postoperative score at Karnofsky performance scale (KPS), duration of the surgical procedure, opioid doses, overall survival and disease-free survival, gender, race, extension of surgical resection and clinical outcome after surgery. To verify the existence of a correlation between quantitative variables, Spearman Test was applied, and, for categorical (qualitative) variables, the Chi-Square Test was used. The Kruskal-Wallis test was applied to assess the variance in means between the groups. Moreover, the log-rank test was applied to assess for survival between groups. The significance level adopted in all tests was 5% (p≤0.05). This study was registered and approved by the ethical committee of the Faculdade de Medicina de Botucatu – UNESP. Results: Analyzing the correlation of the total opioid dosage and the investigated variables, the surgical duration and age at surgery (p=0.029 and 0.003, respectively) were the only ones that showed significant relations. There was no difference regarding the volume of opioids dosage and disease-free survival time (p = 0.86), or the overall survival (p = 0.87). Conclusion: The present study confirms that there is no relationship between intraoperative opioid dose and overall survival and disease-free survival in patients undergoing surgical treatment for Glioblastoma Multiforme.

Introdução: Glioblastoma Multiforme (GBM) é um dos tumores malignos mais agressivos que pode acometer o ser humano. Trata-se de uma neoplasia primária do sistema nervoso central (SNC) que, até o momento, não dispõe de tratamento com perspectiva de cura e tem prognóstico de sobrevida em torno de 7 a 15 meses. Recentemente, o uso de opioides nas cirurgias oncológicas tem sido relacionado a progressão e disseminação da doença. O objetivo desse estudo é investigar a influência do uso intraoperatório de opioide na sobrevida livre de doença e na sobrevida total de pacientes submetidos a cirurgia para GBM. Métodos: Estudo retrospectivo observacional, com análise de prontuários de 133 pacientes que foram submetidos a 167 procedimentos cirúrgicos para ressecção de GBM. Os critérios de inclusão foram: idade maior que 18 anos, pacientes de ambos os sexos, operados de tumor cerebral com confirmação anatomopatológica de GBM. Foram excluídos pacientes que morreram no período pós-operatório de causas não relacionadas à doença de base, assim como aqueles em que não havia dados referentes às doses de drogas utilizadas no peroperatório. Foram analisadas as seguintes variáveis: início dos sintomas, idade, escores pré e pós-operatório na escala de Karnofsky (KPS), duração do procedimento cirúrgico, dose dos opoides, sobrevida livre de doença e sobrevida total, sexo, raça, extensão da ressecção cirúrgica e evolução clínica no pósoperatório. Para verificar a existência de correlação entre as variáveis quantitativas, foi utilizado o teste de Spearman e, para as variáveis categóricas (qualitativas), o teste Qui-Quadrado. O teste Kruskal-Wallis foi aplicado para acessar a variância nas médias entre os grupos de doses diferentes de opioides, e o teste Log-Rank , para acessar a sobrevida entre esses grupos. O nível de significância adotado foi de 5% (p≤0,05). Este estudo foi registrado e aprovado pelo comitê de ética da Faculdade de Medicina de Botucatu – UNESP. Resultados: A análise de correlação da dose de opoide com as variáveis investigadas mostrou significância estatística apenas com a duração da cirurgia e a idade do paciente (p=0,029 e 0,003 respectivamente). Não houve relação entre dose de opioide e sobrevida livre de doença (p=0,86) nem entre essa dose e sobrevida total (p=0,87). Conclusão: O presente estudo confirmou não haver relação entre dose de opioide intraoperatória e sobrevida livre de doença nem sobrevida total em pacientes submetidos a tratamento cirúrgico de GBM.
The impact of intraoperative use of opioids on the survival of individuals undergoing surgery for Glioblastoma Multiforme
Keywords: Glioblastoma; Analgésicos; Opioides; Receptor opioide mu; Sobrevida livre de doença; Analgesics; Opioid; Mu opioid receptor; Disease free survival